High-Speed imaging reveals opposing effects of chronic stress and antidepressants on neuronal activity propagation through the hippocampal trisynaptic circuit - Stepan, Jens; Hladky, Florian; Uribe, Andrés; Holsboer, Florian; Schmidt, Mathias V.; Eder, Matthias (Frontiers in Neural Circuits, 2015)
Antidepressants (ADs) are used as first-line treatment for most stress-related psychiatric disorders. The alterations in brain circuit dynamics that can arise from stress exposure and underlie therapeutic actions of ADs remain, however, poorly understood. Here, enabled by a recently developed voltage-sensitive dye imaging assay in mouse brain slices, we examined the impact of chronic stress and concentration-dependent effects of eight clinically used ADs (belonging to different chemical/functional classes) on evoked neuronal activity propagations through the hippocampal trisynaptic circuitry (HTC: perforant path - dentate gyrus - area CA3 - area CA1). Exposure of mice to chronic social defeat stress led to markedly weakened activity propagations (“HTC-Waves”). In contrast, at concentrations in the low micromolar range, all ADs, which were bath applied to slices, caused an amplification of HTC-Waves in CA regions (invariably in area CA1). The fast-acting “antidepressant” ketamine, the mood stabilizer lithium, and brain-derived neurotrophic factor (BDNF) exerted comparable enhancing effects, whereas the antipsychotic haloperidol and the anxiolytic diazepam attenuated HTC-Waves. Collectively, we provide direct experimental evidence that chronic stress can depress neuronal signal flow through the HTC and demonstrate shared opposing effects of ADs. Thus, our study points to a circuit-level mechanism of ADs to counteract stress-induced impairment of hippocampal network function. However, the observed effects of ADs are impossible to depend on enhanced neurogenesis.